Soilborne microbial plant pathogens and disease management. Volume one, Nature and biology - Narayanasamy, P., 1937- ([S.l.] : CRC PRESS, 2019)
Soilborne microbial plant pathogens including oomycetes, fungi, bacteria and viruses cause several economically important destructive diseases and the symptoms of infection can be recognized only after the pathogen has invaded many tissues primarily vascular tissues of susceptible plants. This condition places formidable challenges in investigating different aspects of host-microbial pathogen interactions. Early detection of infection and precise identification, differentiation, and quantification of the microbial plant pathogens in plants, soil and water sources are essential requirements for development of effective tactics to reduce the incidence and spread of the diseases caused by them. As the microbial plant pathogens differ in their virulence and sensitivity to the environment and chemicals applied, it is imperative to assess the extent of variability in the concerned pathogens. This first volume of a two-volume set introduces disease-causing microorganisms including oomycetes, fungi, bacteria, and viruses found in soils. It focuses on the biology, detection, and identification of soilborne bacterial, fungal, and viral plant pathogens. This volume discusses various techniques based on biological, immunological and genetic properties of the pathogens indicating their advantages and limitations for selecting the appropriate technique to fulfill the requirements. Features: Presents techniques useful for detection, identification, quantification of microbial plant pathogens in plants, soil, and irrigation water from waterbodies. Highlights subversive activities of viruses, resulting in the breakdown of host defense systems. Discusses RNA silencing in infected plants by viruses and posttranscriptional gene silencing (PTGS) functioning as an endogenous mechanism in plants against virus infection. Presents information on methods of assessment of genetic variability and sensitivity of microbial plant pathogens to chemicals and adverse environmental conditions.
OCLC-licensed vendor bibliographic record.
Keywords: Soilborne plant pathogens; Soilborne plant diseases; Soil microbiology; Pathogenic microorganisms; SCIENCE / Life Sciences / Botany; SCIENCE / Life Sciences / General; TECHNOLOGY / Agriculture / General